Sonic Justice and Tree Equity: Exploring Spatial Correlations between Aviation-Related Noise, Demographics, and Tree Canopy - Rodriguez-González, Mayra I; Torres-Garrido, Kevin G (Geoplanning: Journal of Geomatics and Planning, 2023)
The intricate relationship between aviation-related noise pollution, demographic factors, and tree canopy cover can hold significant implications for targeted interventions promoting environmental equity, sonic justice, and sustainable urban development. This study offers a geospatial exploration of these interconnections within the continental United States by employing National Transportation Noise Pollution data from the United States Department of Transportation alongside tree canopy cover from the United States Geological Survey’s National Land Cover Database and demographic data from the American Community Survey in a correlation analysis. Our analysis reveals stark disparities in noise exposure levels, notably underscoring that low-income and predominantly Hispanic neighborhood shoulder a disproportionate burden of aviation-related noise. Moreover, a correlation between aviation-related noise pollution and low tree canopy cover suggests a potential avenue for utilizing nature as a buffer against heightened noise levels. However, recognizing the delicate equilibrium between fostering a thriving tree canopy and ensuring aviation safety highlights a need for innovative urban planning solutions capable of simultaneously addressing sonic injustice and tree inequity.